Sensitive ultra-fast liquid chromatography method for rosmarinic acid determination in Wistar rat’s plasma and brain - Flávia Nathiely Silveira Fachel; Luana Roberta Michels; Juliana Hofstätter Azambuja; Valquíria Linck Bassani; Letícia Scherer Koester; Amelia Terezinha Henriques; Elizandra Braganhol; Helder Ferreira Teixeira (Drug Analytical Research, 2019)
Rosmarinic acid (RA) is a polyphenolic compound recently associated to a neuroprotective potential. Nevertheless, besides the RA poor bioavailability and availability in the central nervous system (CNS) some alternatives to RA delivery, protection, and release been investigated. Recently, our research group optimized chitosan-coated nanoemulsions for RA nasal administration and demonstrated the glioprotective effect against LPS-induced damage in astrocytes. In this context, this study aimed to validate a fast, simplified and stability-indicating UFLC method previously reported by our research group for RA determination in Wistar rat’s plasma and brain, to be employed in further in vivo studies, since the nasal route for RA are not completely understood. The method was validated in terms of specificity, linearity, matrix effect, stability, precision, accuracy and extraction recovery for rat plasma and brain, according to the official guidelines. The method was sensitive, linear (0.1 - 10 µg.mL−1), precise and accurate, and showed RA recovery higher than 85% in plasma and brain. Overall results demonstrated that method was successfully validated for determination of RA in rat plasma and brain matrices with high sensibility and with high recovery using simple extraction processes.